Ankle Brachial Index (ABI) predicts 2-year mortality risk among older adults in the Republic of Congo: The EPIDEMCA-FU study. (July 2019) - Samba, Harielle; Guerchet, Maëlenn; Ndamba-Bandzouzi, Bébène; Kehoua, Gilles; Mbelesso, Pascal; Desormais, Ileana; Aboyans, Victor; Preux, Pierre-Marie; Lacroix, Philippe
Abstract: Background and aims: Peripheral artery disease (PAD) is known to be associated with mortality in high income countries but no data regarding Sub-Saharan Africa (SSA) populations are documented. This study aimed at assessing the prognostic value of the Ankle Brachial Index (ABI) among older adults in the Republic of Congo. Methods: Congolese subjects ≥65 years were included in a longitudinal population-based survey (EPIDEMCA-FU). Demographic, biological, and clinical data were collected at baseline. PAD was defined by an ABI≤0.90. Information on mortality was collected from key informants in participants' households. Cox proportional hazard models, adjusted for traditional and cardiovascular risk factors, were fitted to evaluate the association between an ABI≤0.90 and death. Results: 1029 participants were recruited at baseline. ABI measurement was obtained from 927 participants, of whom 17.4% presented an ABI≤0.90. During a 2-year follow-up, a total of 83 (9.1%) deaths were recorded. Mortality was higher in the low-ABI group with 23 deaths (14.7%) vs. 57 (7.8%) and 3 (12.0%), respectively among those with 0.90 < ABI<1.4 and ABI≥1.40 ( p = 0.039). After adjustment, an ABI≤0.90 was associated with an increased risk of mortality (HR = 1.86; 95%CI 1.04–3.87). Mortality was also independently associated with increasing age (HR = 1.05; 95%CI 1.02–1.09), dementia (HR = 2.73; 95% CI 1.15–8.05), alcohol use (HR = 0.51; 95%CI 0.29–0.88) and female sex (HR = 0.37; 95%CI 0.19–0.72). Conclusions: In this study, a low ABI predicted an increased mortality risk among older people. ABI may represent a simple and inexpensive tool to identify older people at high risk of death in SSA. Graphical abstract: Image 1 Highlights: Peripheral artery disease (PAD) association with mortality in native older Africans is poorly documented. Low ABI (≤0.90) was associated with increased mortality risk in adults >=65 in Congo. ABI may be a reliable tool to identify older people at high risk of death in Sub-Saharan Africa.